All Days 2013
DOI: 10.2118/165486-ms
|View full text |Cite
|
Sign up to set email alerts
|

Key Learnings from a Simulation Study of a Solvent-Assisted SAGD Pilot at Cold Lake

Abstract: ExxonMobil and Imperial Oil Resources (IOR) are conducting a Solvent Assisted - Steam Assisted Gravity Drainage (SA - SAGD) experimental pilot at Cold Lake in the Clearwater formation. In this SA-SAGD pilot, up to 20% by volume of a hydrocarbon solvent (diluent) has been injected along with dry steam in a dual horizontal well SAGD configuration. The primary objective of the pilot was to quantify the impact of solvent addition on bitumen production and steam-oil ratio (SOR). Key surveillance data collected duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…17 Recently, thermal solvent methods such as solvent-assisted SAGD (SA-SAGD) have been applied to real reservoirs and showed promising results. 18,19 Semianalytical models have also been developed to model this process. 20 Leyva-Gomez and Babadagli in 2017 numerically modeled heavy oil recovery from oil sands with a high-temperature solvent, and they showed that the process is highly sensitive to temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…17 Recently, thermal solvent methods such as solvent-assisted SAGD (SA-SAGD) have been applied to real reservoirs and showed promising results. 18,19 Semianalytical models have also been developed to model this process. 20 Leyva-Gomez and Babadagli in 2017 numerically modeled heavy oil recovery from oil sands with a high-temperature solvent, and they showed that the process is highly sensitive to temperature and pressure.…”
Section: Introductionmentioning
confidence: 99%